2004
DOI: 10.1016/j.physletb.2004.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of degenerate sterile neutrinos on the supernova neutrino flux

Abstract: We consider the possibility that there exist sterile neutrinos which are closely degenerate in mass with the active neutrinos and mixed with them. We investigate the effects of this kind of active-sterile neutrino mixing on the composition of supernova neutrino flux at the Earth. If an adiabatic MSW-transition between active and sterile neutrinos takes place, it could dramatically diminish the electron neutrino flux.Comment: 12 pages. Final version to be published in Phys. Lett.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…For example, sterile neutrinos could, if created in conversion processes, carry away a significant amount of explosion energy and influence the dynamics of the QN. These kinds of neutrino models have been extensively studied in connection with supernovae, and it is found that sterile neutrinos with masses in the keV range may lead to conversions, but very heavy or light sterile neutrinos have no resonances inside the core or envelope (see, e.g., Abazajian et al 2001;Keränen et al 2004). We do not consider the possibility of sterile neutrinos further in this work.…”
Section: Neutrino Oscillations and Matter Effectsmentioning
confidence: 99%
“…For example, sterile neutrinos could, if created in conversion processes, carry away a significant amount of explosion energy and influence the dynamics of the QN. These kinds of neutrino models have been extensively studied in connection with supernovae, and it is found that sterile neutrinos with masses in the keV range may lead to conversions, but very heavy or light sterile neutrinos have no resonances inside the core or envelope (see, e.g., Abazajian et al 2001;Keränen et al 2004). We do not consider the possibility of sterile neutrinos further in this work.…”
Section: Neutrino Oscillations and Matter Effectsmentioning
confidence: 99%
“…Low-mass sterile neutrinos mixed with active ones can strongly modify the neutrino signal from a core-collapse SN and r-process nucleosynthesis in the neutrino-driven wind [21,[45][46][47][48]. These effects should be studied in the presence of two sterile flavors and CP violating phases.…”
mentioning
confidence: 99%
“…Low-mass sterile neutrinos mixed with active ones can strongly modify the neutrino signal from a core-collapse SN and r-process nucleosynthesis in the neutrino-driven wind [21,[45][46][47][48]. These effects should be studied in the presence of two sterile flavors and CP violating phases.…”
mentioning
confidence: 99%